Recent advancement in Epilepsy Surgery - Dahal, Rizu; Gurung, Pritam; Shrestha, Resha; Pant, Basant (Nepal Journal of Neuroscience, 2024)
Epilepsy surgery has evolved from a limited, high-risk intervention to a sophisticated, multifaceted option for patients with drug resistant epilepsy (DRE). The journey of this field highlights the growing ability of neurosurgeons to target specific areas within the brain to achieve meaningful outcomes, offering new hope for patients who were once thought untreatable. With new advancements, particularly in deep brain stimulation (DBS)/ lesioning and stereoelectroencephalography (SEEG), epilepsy surgery now stands at the forefront of precision and innovation.